2014
DOI: 10.1007/s10661-014-3825-3
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds as bioindicators of heavy metals off a hot spot area on the Egyptian Mediterranean Coast during 2008–2010

Abstract: Concentrations of Cu, Zn, Cd, Pb, Ni, Co, Fe, Mn, and Hg were measured successively in water, sediments, and six macroalgal species belonging to three algal classes during 3 years (2008-2010) from Abu Qir Bay, Alexandria, Egypt: Chlorophyceae (Enteromorpha compressa, Ulva fasciata), Phaeophyceae (Padina boryana), and Rhodophyceae (Jania rubens, Hypnea musciformis, Pterocladia capillacea). The study aimed to assess the bioaccumulation potential of the seaweeds, as well as to evaluate the extent of heavy metal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Mn concentration varied from 17.70 to 85.36 mg/kg, where the highest Mn content was detected in J. rubens while the lowest level was noted in U. fasciata , collected from Abu Qir Bay. Lower value of Mn 59.97 mg/kg was reported for J. rubens by Shams El-Din et al [ 69 ] but a comparable level was observed for U. fasciata 16.01 mg/kg.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Mn concentration varied from 17.70 to 85.36 mg/kg, where the highest Mn content was detected in J. rubens while the lowest level was noted in U. fasciata , collected from Abu Qir Bay. Lower value of Mn 59.97 mg/kg was reported for J. rubens by Shams El-Din et al [ 69 ] but a comparable level was observed for U. fasciata 16.01 mg/kg.…”
Section: Resultssupporting
confidence: 53%
“…The highest concentration of Ni was recorded in the green seaweed U. fasciata collected from Abu Qir Bay (5.51 mg/kg); however, the lowest level of Ni residue was observed in J. rubens (2.10 mg/kg). Shams El-Din et al [ 69 ] reported lower concentration of Ni as 3.64 mg/kg in U. fasciata and higher Ni level of 11.97 mg/kg in J. rubens collected from the same area.…”
Section: Resultsmentioning
confidence: 99%
“…The cell wall polysaccharides of macroalgae contain multiple functional groups, i.e., anionic carboxyl, amino, sulfhydryl, sulfate, and phosphate responsible for the high complexation of metallic cation from its surroundings [76]. They accumulate most of these metals without suffering any cell damage [77]. The macro, trace, and toxic elements differ widely in seaweed [78].…”
Section: Discussionmentioning
confidence: 99%
“…at longitudes 30°07' E and latitudes 31°16' N. The bay is a hot spot area since it is subjected properly to discharge of primary treated sewage water, in addition to fishing activities. As well as, a discharge of industrial wastewater through "Tabia Pumping Station" and the agricultural effluents from Lake Edku (Shams El-Din et al, 2014). This area is affected by the eastward windinduced current (El-Tawil and Khalil, 1983).…”
Section: The Study Areamentioning
confidence: 99%